Adesivos termofundíveis : correlação da natureza química com suas propriedades adesiva, reológica e térmica - Freitas, Renata Fialho Rocha (2016)
Hot melt adhesives have the advantage that doesn’t liberate volatile organic compounds as solvent borne adhesives, and the consumption of these adhesives is growing up. The application of these adhesives covers various areas as packages, shoes, furniture and others. Thus, this study aims to evaluate the hot melt adhesion and interaction of different chemical natures (polyamide, polyurethane, EVA, HMPSA basis of rubber and polyolefin) with different substrates (TPU, PVC, TR, synthetic leather and leather). To evaluate the interaction between adhesive-substrate and to characterize adhesives and substrates were used the techniques: rheology, contact angle, FTIR, DRX, roughness analysis, NMR-1H, SEM, AFM, DSC, GPC and DMTA. Through determining the surface energy and the dispersive and polar components of adhesives and substrates by contact angle, it was possible to calculate work of adhesion and compare with the bonding performance. From this, it was observed that polyurethane adhesives showed better bonding performance than other adhesives. Between polyurethanes adhesives has been found that polyurethanes with higher work of cohesion, work of adhesion and dissipate less energy tend to promote better bonding performance, this result is associated with the ratio between soft and hard segments of polyurethanes.